International review of social history, vol. 55, part 3 - december 2010
- Fernando Teixeira da Silva, 'The Brazilian and Italian Labor Courts: Comparative Notes' - Erik Green, 'State-led Agricultural Intensification and Rural Labour Relations: The Case of Lilongwe Land Development Program in Malawi, 1968-1981' - Kathryn Oberdeck, 'Of Tubs and Toil: Kohler Workers in an Empire of Hygiene, 1920-2000' Survey - Rüdiger Hachtmann, 'Fordism and Unfree Labor: Aspects of the Work Deployment of Concentration Camp Prisoners in German Industry between 1941 and 1944' Review Essay - Matthias Middell, 'The Global Proletariat after the Model of the Doubly Free Wage Laborer?'